Cytotoxic and anti-inflammatory salicin glycosides from leaves of Salix acmophylla. (September 2016) - Shah, Zafar Ali; Hameed, Attiya; Ahmed, Aqeel; Simjee, Shabana U.; Jabeen, Almas; Ullah, Abid; Shaheen, Farzana
Graphical abstract: Highlights: Two new salicin glycosides of Salix acmophylla, were characterized. Their structures were elucidated by extensive NMR studies. New compound, acmophyllin A (1 ), was identified as cytotoxic constituent of plant. Two known isolates showed potent inhibition of intracellular ROS production. Abstract: The species of genus Salix, commonly known as Willow, are well known worldwide as rich source of medicinally important salicin derivatives and phenolic glycosides. The current study focuses on Salix acmophylla Bioss with the aim of identifying new bioactive constituents of this plant. Two new salicin glycosides, acmophyllin A (1 ), acmophyllin B (2 ) and five reported phenolic glycosides3–7, were identified from S. acmophylla Bioss. NMR and mass spectroscopic techniques were employed to elucidate the structure of secondary metabolites of S. acmophylla . The new salicin glycosides were evaluated against three different cancer cell lines i.e., PSN-1 (pancreatic cancer cells), MCF-7 (breast cancer cells) and NCI-H460 (lung cancer cells). The acmophyllin A (1 ) exhibited cytotoxicity in a dose dependent manner against all three cancer cells (IC50 ∼35–40 μM). Acmophyllin B (2 ) exhibited mild activity against PSN-1 cells and MCF-7 cancer cells. In addition, compounds5 and6 showed potent inhibition of oxidative burst in zymosan activated neutrophils by chemiluminescence technique, while no other compound were found to inhibit the production of reactive oxygen species (ROS).